Pets in Advertisements. A Socio-Semiotic Key to Interpretation - Boero, Marianna (E|C, 2020)
For some years now, advertising has shown a new, but growing, protagonism of pets, increasingly humanized and inserted in contexts of daily life on a par with other family members. To understand the mechanisms underlying this change, in the following paragraphs we will focus on three different, but related, fields of investigation: social advertising, commercial advertising and web videos, starting from a general picture of the new consumer context and then arriving, to a more specific extent, to a case study. The objective is to reconstruct the path of change that has been outlined over the years and to understand if in it we can see traces of a socio-cultural change that also affects the way social relationships and family models are conceived. The reading key that we propose is therefore sociosemiotic: from this point of view, the set of communications that put pets at the center of our discourse influence our way of understanding the "real" and are at the same time indicative of new emerging sensitivities.